Business Ethics in the Algorithmic Era: A Challenge Consumer Data Privacy and PDP Regulation - Saepulloh, Yusep; Andi, Rendi Rizki (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Amidst the euphoria of Industrial Revolution 4.0 and Society 5.0, data has emerged as